China’s New Environmental Protection Law and Green Innovation: Evidence from Prefecture-Level Cities - Wen Chen; Ying Wu (Complexity)
This paper examines the impact of China’s new environmental protection law on green innovation. Using a large sample of Chinese prefecture-level cities for the 2010–2016 period and the difference-in-differences (DID) methodology, we provide strong evidence that the new environmental protection law promotes green innovation. This finding is robust to a battery of sensitivity tests. The micromechanism analysis shows that the new environmental protection law can promote green innovation by imposing stricter financial constraints on enterprises in high-pollution industries and increasing their incentives for green innovation to meet green credit requirements. Further, we find that the impact of the new environmental protection law on green innovation is more prominent in prefecture-level cities with a lower level of banking competition and for prefecture-level cities with stronger intellectual property protection. Overall, these findings suggest that the new environmental protection law has played an important role in promoting green innovation in China. To improve the effect of the new environmental protection law on green innovation, the government can consider lowering banking competition and strengthening intellectual property protection.